Enantioseparation of mandelic acid on vancomycin column: Experimental and docking study. Issue 11 (14th August 2020) - Shahnani, Mostafa; Sefidbakht, Yahya; Maghari, Shokoofeh; Mehdi, Ahmad; Rezadoost, Hassan; Ghassempour, Alireza
Abstract: So far, no detailed view has been expressed regarding the interactions between vancomycin and racemic compounds including mandelic acid. In the current study, a chiral stationary phase was prepared by using 3‐aminopropyltriethoxysilane and succinic anhydride to graft carboxylated silica microspheres and subsequently by activating the carboxylic acid group for vancomycin immobilization. Characterization by elemental analysis, Fourier transform infrared spectroscopy, solid‐state nuclear magnetic resonance, and thermogravimetric analysis demonstrated effective functionalization of the silica surface. R and S enantiomers of mandelic acid were separated by the synthetic vancomycin column. Finally, the interaction between vancomycin and R / S mandelic acid enantiomers was simulated by Auto‐dock Vina. The binding energies of interactions between R and S enantiomers and vancomycin chiral stationary phase were different. In the most probable interaction, the difference in mandelic acid binding energy was approximately 0.2 kcal/mol. In addition, circular dichroism spectra of vancomycin interacting with R and S enantiomers showed different patterns. Therefore, R and S mandelic acid enantiomers may occupy various binding pockets and interact with different vancomycin functions. These observations emphasized the different retention of R and S mandelic acid enantiomers in vancomycin chiral column. Abstract :